English Games (Bermain Peran) Untuk Meningkatkan Hasil Belajar Bahasa Inggris Siswa Kelas IX SMP - L. Darmat (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of study namely (1) Describe the learning process of speaking skills in English subjects using English games (Role Playing) and (2) Describe the results of the process of implementing speaking skills in English using English games ( Role Playing) in grade IX students of SMP. This type of research is Classroom Action Research (CAR). The results of the study show that the increase in speaking ability is indicated by the class average values that have been obtained. At the time before the action is carried out, the class average value obtained is 63.51. After carrying out the action in the first cycle the grade average value is 70.55. In the second cycle, the average grade increases, the class average increases to 78.70. Aside from the average class score, the achievement of KKM scores also increased, namely the action of KKM achievement of 22%, in the first cycle the achievement of the KKM value was 44%, and the second cycle the achievement of the KKM value increased 85%. Thus it can be concluded that the English game (role playing) can improve the speaking skills and motivation of students in English subjects.